2018
DOI: 10.1007/s10493-018-0267-6
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting next season’s Ixodes ricinus nymphal density: the example of southern Germany 2018

Abstract: The castor bean tick, Ixodes ricinus (L.) (Ixodida: Ixodidae), is the principal vector of pathogens causing tick-borne encephalitis or Lyme borreliosis in Europe. It is therefore of general interest to make an estimate of the density of I. ricinus for the whole year at the beginning of the tick season. There are two necessary conditions for making a successful prediction: a long homogeneous time series of observed tick density and a clear biological relationship between environmental predictors and tick densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 25 publications
5
43
1
2
Order By: Relevance
“…Numerous empirical studies have shown that Ixodes ticks and tick-borne diseases are emerging public health problems at the northern limit of their geographic distribution [8,[57][58][59]. In contrast, fewer studies have investigated whether global warming has influenced Ixodes tick abundance in areas where Lyme disease is endemic [10][11][12][13][14][15][16][17]. The present study did not find direct links between climate change and the observed doubling in tick abundance.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Numerous empirical studies have shown that Ixodes ticks and tick-borne diseases are emerging public health problems at the northern limit of their geographic distribution [8,[57][58][59]. In contrast, fewer studies have investigated whether global warming has influenced Ixodes tick abundance in areas where Lyme disease is endemic [10][11][12][13][14][15][16][17]. The present study did not find direct links between climate change and the observed doubling in tick abundance.…”
Section: Discussioncontrasting
confidence: 83%
“…Another 8-year study in central New Jersey, USA, found no significant directional change in the abundance of I. scapularis nymphs [12]. Other long-term studies have found large inter-annual fluctuations in density, but none of them found that Ixodes tick density was increasing [10,13,14]. Increased tick abundance could have important consequences for the incidence of tick-borne diseases and public health.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The majority of nymphal ticks belonging to the I. ricinus species complex were collected from April to June (61.8%). In the extraordinary tick year 2018 (Brugger et al 2018), almost 20% more nymphal ticks and 12× more adults were collected at the site Klosterneuburg than in the same period of the previous year.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, an estimation of the questing tick density by using a standardized sampling method is essential. Time series of questing tick densities were recently used to compile tick density maps for Germany (Boehnke et al 2015;Brugger et al 2016), to investigate seasonal cycles of the tick density (Brugger et al 2017), and to develop models to forecast the next season's tick densities (Brugger et al 2018).…”
Section: Introductionmentioning
confidence: 99%